Land and agriculture in the Philippines an economic history perspective - Corpuz, O. D. (1992)
This article explains the land system established since the late 16th and 17th centuries as a result of the Spanish conquest, and traces the various types of landholdings and their economic roles to the end of the Spanish era. Except for the government purchase of the friar haciendas in 1903, the structure of the land system - and of agriculture - was not changed during the United States occupation era. The cadastering and titling systems favored large landholders and plantation agriculture, and small scale agriculture, especially the rice sector, was neglected. The article closes with a presentation of average farm sizes covering 1903 (good for 1898) to 1980, showing the fragmentation of farms in domestic agriculture.
Keywords: Land reform; Agriculture and state